Rural-urban migration in D-dimensional lattices - Espindola, A. L.; Penna, TJP; Silveira, J. J. (World Scientific Publ Co Pte Ltd, 2005)
The rural-urban migration phenomenon is analyzed by using an agent-based computational model. Agents are placed on lattices which dimensions varying from d = 2 up to d = 7. The localization of the agents in the lattice defines that their social neighborhood (rural or urban) is not related to their spatial distribution. The effect of the dimension of lattice is studied by analyzing the variation of the main parameters that characterizes the migratory process. The dynamics displays strong effects even for around one million of sites, in higher dimensions (d = 6, 7).
Keywords: econophysics; rural-urban migration; Monte Carlo methods; computational modelling